Analisis Birokrasi Pemerintah Dalam Penanganan Bencana - Syafaruddin Syafaruddin; A.M. Fadli Mappisabbi; Nurasia Natsir (Universitas 17 Agustus 1945, 2024)
Natural and non-natural disasters often have widespread impacts on society. In such emergencies, the role of government bureaucracy becomes crucial in providing a rapid and effective response and management. However, the performance of government bureaucracy in disaster management is often still questioned, both in terms of coordination, resource allocation, and the accuracy of actions. This study aims to evaluate the role and performance of government bureaucracy in responding to and managing disaster situations, as well as to identify the factors that influence the effectiveness of bureaucracy in disaster management. The research method used is a case study with a qualitative approach. Data collection is done through in-depth interviews with relevant stakeholders, field observations, and document analysis. The research results are expected to provide a more comprehensive understanding of the role and performance of government bureaucracy in disaster management. In addition, this research can also identify key factors that influence the effectiveness of bureaucracy, both internal (organizational structure, culture, leadership) and external (inter-agency coordination, resource support). The findings of this research can be input for the government in formulating policies and strategies to enhance the capacity of bureaucracy in disaster management in the future.